Relationship of Media and Information Literacy and the Ability to Spot Political Misinformation Among Learners in SHS in San Nicholas III, Bacoor City - Navo, Maria Theresa (Animo Repository, 2023)
Prevalence of political misinformation among the learners in the Philippines is seen as a serious threat to democracy. The study was conducted to determine if there is a relationship between media and information literacy and the ability to spot political misinformation among learners in SHS in San Nicholas III, Bacoor City. Correlational-descriptive research design was used in the study. Three hundred fifty-two learners were used as respondents of this study. The socio-demographic profile of the learners in terms of sex, grade level and strand were gathered. Media and Information Literacy rate of the learners and their ability to spot political misinformation were measured using adapted questionnaires. Data were analyzed using one-way analysis of variance, t-test, and Pearson’s correlation coefficient. Results revealed that media and information literacy of the learners are advanced with a mean score of 4.12. The ability of the learners to spot political misinformation is fair with a mean score of 6.79. There was no significant difference in the learner’s media and information literacy in terms of their sex, grade level and strand. Moreover, there was no significant difference found in the learners’ ability to spot political misinformation in terms of their grade level, but a significant difference was found in terms of their sex and strand. The findings conclude that despite having advanced media and information literacy, the learners can still have a fair ability in spotting political misinformation.